Attitudes and Willingness to Accept Long-Acting Injections for Patients With Schizophrenia in Beijing: A Cross-Sectional Investigation Based on Samples From the Communities - Zhu, Junli; Chen, Yun; Lu, Wei; Huang, Qingzhi; Li, Bin; Xu, Ying; Xi, Rui; Jin, Lefan (Frontiers in Public Health, 2021)
Background: Schizophrenia has brought a serious disease burden to China. Under the background that community rehabilitation has become the mainstream treatment model, the long-acting injection (LAI) can better prevent recurrence. Some districts in Beijing have also issued policies. This article aims to find out patient’s current attitudes towards LAI and provide policy suggestions. Methods: A representative sample of patients with schizophrenia in the community is selected. Self-made questionnaire to conduct face-to-face interviews to obtain information about the willingness, attitude and reasons for accepting LAI treatment. Use descriptive statistics, t-test and F-test for data analysis. Results: About 10% of respondents have had experience using LAI and the current utilization rate is 2.4%. Respondents' willingness to accept LAI is generally low (only 18.1% are willing). The main reason for willingness is no need to take medication every day, while the main reasons for unwillingness are high cost, fear of injection and lack of understanding. Conclusion: Beijing community patients are not very optimistic about LAI’s cognition and willingness. Medication habits play an important role in their medication selection decisions. Intervention such as educate clinicians and patients about LAI and provide free injections to patients can be imposed. The promotion of LAI still has a long way to go.